2007
DOI: 10.1021/om0701874
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and NHC Lability of d0 Lithium, Yttrium, Titanium, and Zirconium Amido Bis(N-heterocyclic carbene) Complexes

Abstract: The synthesis of lithium(I) complexes of the neutral and anionic salts of a tridentate aminobis(Nheterocyclic carbene) ligand, L, are reported (L ) N{CH 2 CH 2 (1-C[NCHCHNMes])} 2 ), along with the X-ray diffraction determined molecular structure of the imidazolium proligand [H 2 N{CH 2 CH 2 (1-HC-[NCHCHNMes])} 2 ][Br] 3 (H 4 LBr 3 ). The transamination reaction between the lithium chloride adduct of HL and Y[N{SiMe 3 } 2 ] 3 affords yttrium amidocarbene complexes, while the transamination reaction between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(35 citation statements)
references
References 32 publications
2
33
0
Order By: Relevance
“…This is at a higher frequency than observed for unsaturated yttrium-carbene complexes, and compares with d = 186.3 ( [35] [36] and…”
Section: Thesupporting
confidence: 71%
“…This is at a higher frequency than observed for unsaturated yttrium-carbene complexes, and compares with d = 186.3 ( [35] [36] and…”
Section: Thesupporting
confidence: 71%
“…Of note, tridentate bis(amido)-NHC [NCN] pincer complexes of zirconium and hafnium have been reported, 26,27 and amido-bis(NHC) [CNC] and amido-NHC [C,N] complexes of some early and late transition metals are also known. [28][29][30][31][32][33][34][35] Most closely related to this work, Douthwaite has described the palladium [CNC] complex A and, during the course of our research, Luo has reported the Pd complexes (B). 36,37 Fig .…”
Section: Introductionmentioning
confidence: 90%
“…In 2010, Mindiola and co-workers reported the synthesis of the related bridging 98. When more bulky phosphines were used, two remarkable mononuclear complexes,…”
Section: Reactions With Phosphorus-containing Moleculesmentioning
confidence: 99%
“…In addition, dihalide species LYCl 2 , 107, were prepared by salt metathesis between anhydrous YCl 3 and LLi. Although the addition of phosphine oxides to LYClN(SiMe 3 ) 2 resulted in decomposition, discrete, albeit somewhat thermally sensitive (when R ¼ Ph), complexes LYCl 2 (O¼PR 3 ) (R ¼ Me, Ph), 108, were isolated when the same phosphine oxides were reacted with 107 (Scheme 49) [98].…”
Section: Reactions With Phosphorus-containing Moleculesmentioning
confidence: 99%